Pre-participation cardiovascular screening of elderly wrestlers - Farahani, A. V.; Asheri, H.; Alipour, S.; Amirbeigloo, A. (Asian Journal of Sports Medicine, 2010)
Purpose: Sudden death of a competitive athlete is a tragedy that is usually caused by a previously unsuspected cardiovascular disease. The aim of this study was to clarify the role of noninvasive testing in pre-participation cardiovascular evaluation of elderly wrestlers.